Jews on the frontier : religion and mobility in nineteenth-century America - Rabin, Shari (North American religions., 2017)
'Jews on the Frontier' is a religious history of the United States that begins in an unexpected place: on the road with mobile Jews. It follows them out of eastern cities and into the American frontier, where they found unprecedented economic opportunity but also anonymity, loneliness, instability, mistrust, scarcity, and diversity, all of which complicated the many legal obligations of traditional Jewish life.